Antilymphocyte Antibodies in Systemic Lupus Erythematosus: Association with Disease Activity and Lymphopenia. (17th April 2014) - Li, Chun; Mu, Rong; Lu, Xiao-yan; He, Jing; Jia, Ru-lin; Li, Zhan-guo
Abstract : Purpose . We analyzed the prevalence, clinical correlation, and the functional significance of ALA in patients with systemic lupus erythematosus (SLE). Methods . ALA IgG was detected by indirect immunofluorescence in the serum of 130 SLE patients, 75 patients with various rheumatic diseases, and 45 healthy controls (HC). Results . The sensitivity and specificity of ALA IgG in SLE were 42.3% and 96.7%, respectively. ALA was observed in 55.6% (50/90) of patients with lymphopenia, which was significantly higher than in patients with normal lymphocytes (5/40, 12.5%; P < 0.001 ). Patients with active SLE showed higher ALA positivity (60.9%) than those with inactive disease (24.2%; χ 2 = 17.925; P < 0.001 ). ALA correlated significantly with hypocomplementemia, anti-dsDNA antibodies, and higher SLEDAI scores. The incidences of ALA in SLE patients who were seronegative for anti-dsDNA, anti-Sm, or both antibodies were 32.9% (26/79), 41.0% (43/105), and 32.4% (22/68), respectively. The ALA-positive group also had higher incidences of neuropsychiatric SLE (NPSLE) and lupus nephritis (LN). In multivariate analyses, ALA was independently associated with lymphopenia, higher SLEDAI scores, and increased risk for LN. ALA titers significantly decreased as clinical disease was ameliorated following treatment. Conclusions . ALA occurred more frequently in patients with active SLE and was independently associated with lymphopenia, disease activity, and LN.